Frontispiece: Rhodium Complexes Promoting C−O Bond Formation in Reactions with Oxygen: The Role of Superoxo Species. Issue 22 (19th April 2017) - Vilella‐Arribas, Laia; García‐Melchor, Max; Balcells, David; Lledós, Agustí; López, José A.; Sancho, Sofía; Villarroya, B. Eva; del Río, M. Pilar; Ciriano, Miguel A.; Tejel, Cristina
Abstract : Activation of molecular oxygen with a further addition of the oxygen atoms to olefinic C=C bonds mediated by rhodium starts with the formation of an open‐shell triplet mononuclear superoxide complex as revealed by DFT calculations. This event is ensued by the binding of the superoxide to a second molecule of the rhodium starting complex to follow a dinuclear pathway in which the O−O bond is further cleaved. Then, each oxygen atom inserts into a rhodium olefin bond. Details about this contribution can be found in the Full Paper by C. Tejel, A. Lledós et al. onpage 5232 ff.